Predatory ability of Sycanus annulicornis Dohrn. (Hemiptera: Reduviidae) on nettle caterpillar prey (Setora nitens Walker.) (Lepidoptera: Noctuidae) in the laboratory - Rusli Rustam; Dwi Yuwanda Nasution; Yunandra Yunandra; Mukhlis Ibrahim (Journal of Entomological and Acarological Research)
The nettle caterpillar (Setora nitens) is a major pest affecting oil palm plants and is predominantly found in oil palm plantations in Riau. The predator Sycanus annulicornis Dohrn is a potential natural enemy for controlling S. nitens. This study aims to evaluate the predatory ability of S. annulicornis imago when preying on S. nitens. The research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, Riau University, from March to July 2023. The experiment was designed using a completely randomized design method consisting of three treatments with seven replications. The treatments involved S. annulicornis imago [N1=one male imago, N2=one female imago, and N3=one pair of imago (male and female)], with observation parameters including first and second prey search time, prey handling time, predation ability, and total predation. Results showed that the handling time for one S. nitens by S. annulicornis ranged from 3.86 to 5.14 hours. The treatment involving one pair of S. annulicornis imago was the most effective, as it resulted in the fastest prey search times (0.79 minutes for the first prey and 0.71 minutes for the second prey), as well as the fastest prey handling time (3.86 hours), with a total predation rate of 100% for S. nitens.